Impacto das doações filantrópicas e da governança corporativa no desempenho de empresas de capital aberto no Brasil e nos Estados Unidos antes e durante a pandemia (2010-2021) - Franck, Alison Geovani Schwingel (2023)
The main objective of this study is to verify whether the monetary donations made by companies (fruits of corporate philanthropy) mitigate dysfunctional governance problems in relation to performance. In addition, given the pandemic context, it aims to determine whether philanthropic companies increased their performance when compared to other companies during the COVID-19 pandemic and to compare the performance of Brazilian philanthropic companies with American philanthropic companies in relation to confrontation of the pandemic. To this end, the research was divided into 3 studies. The first sought to verify for a sample of Brazilian companies, through a GMM Sys model, whether pecuniary donations made by such companies mitigate dysfunctional governance problems in relation to performance. It was confirmed, even partially, that greater executive compensation increases incentives for philanthropic donations and that the presence of women on the board increases the probability of philanthropic donations, both generating greater performance for companies. The second sought to analyze, through a difference-in-differences model, whether Brazilian philanthropic companies increased their performance compared to other companies during the COVID-19 pandemic. It was confirmed that these companies increased their performance during the period. The third drew a comparison between Brazilian philanthropic companies and American philanthropic companies in relation to the confrontation of the pandemic. Also using a difference-in-differences model for American data, it was found that American companies had a greater positive effect on performance during the pandemic than Brazilian companies. The contributions of this research include the discussion in greater depth on the reciprocal relationship between companies and society, as well as the discussion on the role of corporate governance as a moderator of business performance. Furthermore, it used real data and statistical instruments and made it possible to provide information on the impact of corporate donations on corporate governance and in the performance of companies during global crises.